(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research article explores R.K. Narayan’s representations of women in Indian society, with a specific focus on his novel "The Guide". The study examines how the author’s portrayal of female characters reflects the gender dynamics and cultural norms prevailing in Indian society at that time. By analyzing the complex relationships between Rosie, Marco, and Raju, the article highlights the significant role played by women in the narrative and emphasizes their resilience and determination against societal challenges. Furthermore, the article scrutinizes the transformation of Rosie from a submissive and dependent character to an empowered and independent individual as an iconic reflection of women’s evolution in India during that era. Through a comprehensive analysis of "The Guide", this research contributes to a broader understanding of R.K. Narayan’s literary works and their impact on Indian literature and society. In this article, we will analyze R.K. Narayan’s novel "The Guide" to explore his depictions of women and their role in Indian society. By examining the characters and themes throughout the book, we will discuss how Narayan’s representations demonstrate an evolving worldview within the context of both tradition and modernity